PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR MATERI MERODA PADA SENAM LANTAI KELAS VIII SMP NEGERI 13 SEMARANG TAHUN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of teaching physical education in schools through the use of audio-visual media aids the learning outcomes gymnastics floor meroda the eighth grade students of SMP Negeri 13 Semarang. In this research, a classroom action research (CAR ) cycle , the study was conducted in two cycles of action . Methods of data collection using the methods of documentation , observation , and testing . Analysis of the data using descriptive method by way of student learning outcomes after the action . Based on the results obtained by the use of audio-visual media in the learning material meroda floor exercises can improve learning outcomes eighth grade at Junior High School 13 Semarang 2013/2014 . This is evidenced by the acquisition value of the learning outcomes of each cycle has increased . The average value of students in the first cycle the average test score of students reached 70.51 , reaching 84.72 in the second cycle . Classical completeness in the first cycle of 54.84 % and the second cycle was 90.32 % . From the research results obtained it can be concluded that the learning material meroda floor exercises with the use of audio-visual media can improve learning outcomes students of SMP Negeri 13 Semarang .